To the problem of the new world order: summing up - Plashchinsky, Alexander A. (Journal of the Belarusian State University. Sociology, 2019)
This article contains the main scientific results of our research of the problem of the new world order. It is demonstrated that the historical tendency of certain forces striving towards world hegemony, that is suppressing other nations in order to establish control over their resources and, thus establishing the new world order, appears as being one of the root causes of international conflicts. Their attempts of transforming the system of international relations and establishing global governance caused World War I, World War II, Cold War, «War on Terror», which evolved into todayʼs «hybrid war». The necessity of creating the Eurasian Confederation to prevent the possibility of a global inter-civilizational conflict is being justified. Generalizing conclusion has been made concerning the interdependence of the war and peace problem and the phenomenon of the new world order. This fact allows us to understand the general laws of the historical process and, based on knowledge of the deep trends within world politics, to undertake a search for possible ways of peaceful development of themankind.
Keywords: world politics; new world order; paradigm; war; global governance; Eurasian integration; alliance; national idea